Network-based analysis of dynamical systems : methods for controllability and observability analysis, and optimal sensor placement /: methods for controllability and observability analysis, and optimal sensor placement. ([2020]) - Leitold, Dániel; Abonyi, Janos, 1974-; Vathy-Fogarassy, Ágnes
No abstract available